The "fit but fat" concept revisited: population-based estimates using NHANES - Duncan Glen E (BMC, 2010)
Abstract Low cardiovascular fitness is an independent risk factor for type 2 diabetes and cardiovascular disease in adults. The "fit but fat" concept suggests that cardiovascular fitness attenuates risk of metabolic and cardiovascular disease independent of body mass index (BMI), even among the obese. However, the proportion of U.S. adults considered both fit and obese is unknown. Thus, the purposes of this short paper were to estimate the proportion of U.S. adults who are obese yet have a high cardiovascular fitness level (fit but fat), and determine the independent effect of obesity on cardiovascular fitness. The study was a secondary data analysis of 4,675 adults (20-49 years) who completed a submaximal exercise test, from the National Health and Nutrition Examination Survey (1999-2002). Cardiovascular fitness and body weight were expressed as continuous (estimated VO2max [ml.kg-1.min-1] and BMI [kg/m2]) and categorical variables (low, moderate, and high cardiovascular fitness level; normal weight, overweight, and obese), the later using sex and age-specific criteria from the Aerobics Center Longitudinal Study and standard BMI cut-points, respectively. Using these methods, the prevalence of meeting the fit but fat definition among U.S. adults was 8.9% (95% C.I. = 6.9 - 10.9%), whereas 17.4% were overweight and high fit, and 30% were normal weight and high fit. Importantly, the proportion of low, moderate, and high cardiovascular fitness differed significantly (p < 0.05) by BMI level. Using multiple regression, being obese was associated with a 9.2% lower estimated VO2max compared to being normal weight, even after controlling for age, sex, race/ethnicity, and income. These results suggest that a small percentage of U.S. adults can be considered fit but fat, and that obesity is independently associated with reduced cardiovascular fitness. The likely explanation for the low proportion of U.S. adults who can be considered fit but fat is a low level of physical activity, which constributes to both a positive energy balance and low fitness. Thus, engaging obese adults in physical activity that is sufficient to improve cardiovascular fitness may help to reduce not only body weight, but the excess health burden in this population.